2008
DOI: 10.1196/annals.1414.032
|View full text |Cite
|
Sign up to set email alerts
|

Radical Prostatectomy

Abstract: The first radical prostatectomy was performed in 1904. Since then, it has become one of the main treatment options for patients with prostate cancer, especially those with organ-confined disease. As it is the case in all types of malignancies, the treatment choice for the patient with prostate cancer depends on several considerations, the most important of which is the ability of the treatment modality to control disease. This review provides a brief comparison between radical prostatectomy and other main trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Prostate cancer (PC) is one of the most common malignancies in men in Europe and the United States . Local PC is potentially curable with radiation therapy, hormone therapy, and/or radical prostectomy . However, up to 40% of the patients who are diagnosed with localized disease ultimately develop advanced PC, even after initial treatment of local disease .…”
Section: Prostate Cancermentioning
confidence: 99%
“…Prostate cancer (PC) is one of the most common malignancies in men in Europe and the United States . Local PC is potentially curable with radiation therapy, hormone therapy, and/or radical prostectomy . However, up to 40% of the patients who are diagnosed with localized disease ultimately develop advanced PC, even after initial treatment of local disease .…”
Section: Prostate Cancermentioning
confidence: 99%
“…We found that a significant proportion of prostate cancers in Korean men are poorly differentiated, regardless of initial serum PSA level or clinical stage at presentation; such poorly differentiated tumors adversely affect prognosis, causing a greater rate of PSA failure [6]. Radical prostatectomy (RP) is the treatment of choice for men with localized prostate cancer [7,8]. In addition, surgeons can now anatomically dissect the prostate, thus reducing perioperative morbidity during and after RP [9].…”
Section: Introductionmentioning
confidence: 99%
“…Active surveillance, brachytherapy, external beam radiation therapy (EBRT), HT, and RP are the current options for prostate cancer treatment, each with a distinct impact on a patient's health-related quality of life. For many patients with a long life expectancy, RP remains the most effective approach with respect to both oncologic success and maximization of quality of life [1, 128–130]. …”
Section: Discussionmentioning
confidence: 99%
“…Although it is a recent technological advancement, robotic surgery has shown an increasing rate of adoption worldwide. Currently, more than 30,000 patients have undergone this procedure worldwide [1]. Recent literatures have compared RRP and RALP.…”
Section: New Techniques In Rp Surgery and Rp Futurementioning
confidence: 99%
See 1 more Smart Citation